Low-pulverized high-strength bioaviation kerosene desulfurization activated carbon and preparation method thereof

CN122916141APending Publication Date: 2026-10-16LIANYUNGANG JIAAO NEW ENERGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611324893.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-28
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0004]针对脱硫剂粉化、粉末携带问题,现有改性方案均采用单一维度优化手段,技术缺陷突出:其一,仅通过表面覆膜改性,仅能短期缓解表层磨损,流体长期冲刷后覆膜整体剥落,无法解决活性炭载体内部裂纹碎裂问题,粉化抑制效果随运行时间快速衰减;其二,仅依靠单一无机粘结剂强化颗粒强度,粘结层刚性过强、无缓冲能力,油品剪切冲击下粘结界面易开裂,依旧大量产生粉末;其三,仅对活性炭载体进行孔道扩孔重构,未优化颗粒界面结合强度与外层防护结构,颗粒间摩擦产生的粉末无法被有效抑制

Benefits of technology

[0030]This invention has the following advantages: It breaks through the existing one-sided modification approach of desulfurization activated carbon, which only involves single coating, single bonding, or single pore reinforcement. It pioneers a three-layer integrated synergistic modification system: carrier pore whisker reinforcement, rigid-flexible composite bonding of particles, and rare earth self-healing protection on the outer surface. This system fills and seals the carbon's original brittle microcracks by in-situ growth of rare earth aluminosilicate three-dimensional interlocking whiskers within the micropores and mesopores of the activated carbon. Combined with the cross-linking of silica-alumina sol and oil-resistant polyacrylamide polymers to form a rigid-flexible interpenetrating buffer bonding network, it counteracts the powdering caused by particle impact and fluid shear. Simultaneously, a dense silica-alumina protective film with embedded rare earth active sites is constructed on the outer layer of the particles. When the surface layer is locally damaged by high-speed jet fuel, the rare earth sites within the film can immediately induce condensation micro-crosslinking of surrounding silica-alumina hydroxyl groups, achieving self-healing. This provides long-term, full-chain inhibition of submicron carbon powder shedding from the internal matrix of the powder generation, the particle contact interface, and the outer protective surface. The modification process does not clog the carbon pores and can stably maintain a thickness of 900m. 2 With a high specific surface area of ​​over /g and the original sulfide adsorption capacity, the sulfur content of the finished desulfurized aviation kerosene is stable at ≤1ppm. After 1,000 hours of liquid phase scouring test, the powder shedding rate is reduced by more than 50%, and the replacement cycle of downstream supporting filter elements is extended by more than double. This multi-layered powder suppression modification structure, which combines internal skeleton reinforcement, interface stress buffering, and in-situ self-healing in liquid phase, has no relevant disclosure in existing public technologies. It completely solves the inherent defects of traditional single modification schemes such as easy pore clogging, brittle bonding layer, and rapid failure of surface protection. The process conditions are mild and controllable, and it is suitable for the long-term high flow rate and harsh working conditions of HEFA bio-aviation kerosene sulfur absorption tank.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122916141A_ABST
    Figure CN122916141A_ABST
Patent Text Reader

Abstract

The application provides a low-pulverization high-strength bio-jet fuel desulfurization activated carbon and a preparation method, and belongs to the technical field of bio-jet fuel desulfurization activated carbon. A three-layer integrated modification structure is designed: rare earth aluminosilicate whiskers are grown in situ in pores to fill primary microcracks of carbon, a rigid-flexible interpenetrating adhesive layer is formed between particles by silicon-aluminum sol and high-molecular resistance to offset impact shear, and a rare earth silicon-aluminum film is embedded in the outer layer to catalyze hydroxyl condensation and realize liquid-phase self-healing when the oil product is washed and damaged. Four mild processes including hydrothermal pore strengthening, composite extrusion molding, surface solidification and active loading are prepared, the specific surface area of the modified carrier is not less than 900 m 2 / g, the desulfurization capacity does not decay, the pulverization rate is reduced by more than 50% after 1,000-hour liquid-phase washing test, the total sulfur in the treated bio-jet fuel is stable at ≤1 ppm, the powder plugging of the downstream filter element is significantly reduced, the service life of the filter element is doubled, the defects of short-term failure and easy plugging of existing single modification are overcome, and the long-period industrial working condition of HEFA bio-jet fuel sulfur absorption tank is adapted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of activated carbon technology for desulfurization of bio-jet fuel, specifically to a low-pulverization, high-strength activated carbon for desulfurization of bio-jet fuel and its preparation method. Background Technology

[0002] Sustainable aviation fuel (SAF, bio-jet fuel) is a core pathway for the aviation industry to achieve carbon emission reduction throughout its entire lifecycle and ensure aviation energy security. Many countries worldwide have successively introduced mandatory blending policies to promote the large-scale production of bio-jet fuel via the HEFA (Heat-Alkali-Fuel-Oil Hydrogenation) route. The hydrogenation products of bio-jet fuel contain trace amounts of organic sulfur compounds, which require deep liquid-phase adsorption desulfurization using activated carbon-based desulfurizing agents in sulfur absorption tanks. The industry mainstream uses columnar activated carbon loaded with copper salt complexed active components as the desulfurization medium, which can reduce the total sulfur content of jet fuel to below 10 ppm, meeting jet fuel product quality standards.

[0003] Existing commercially available columnar activated carbon carriers inherently possess numerous brittle microcracks, resulting in poor mechanical resistance to erosion and friction. Under conditions of prolonged scouring by high-velocity liquid oil in the sulfur absorption tank and collisions and friction between desulfurizing agent particles, the activated carbon framework is highly susceptible to breakage and detachment, generating a large amount of submicron-sized fine powder. This powder is continuously transported downstream with the jet fuel fluid, and upon entering the downstream jet fuel filter dehydrator, it becomes deeply embedded in the coalescing filter element, disrupting the internal pores of the separation filter element. This causes rapid clogging of the filter element, a continuous increase in system operating pressure differential, and a significant decrease in dehydration and separation efficiency. To maintain stable operation, companies need to frequently replace high-value specialized filter elements, which not only significantly increases spare parts procurement costs but also forces the unit to undergo periodic shutdowns for maintenance, reducing the continuous production cycle of bio-jet fuel. This is a common technical pain point in the current HEFA process bio-jet fuel production industry.

[0004] To address the issues of desulfurizer pulverization and powder carryover, existing modification solutions all employ single-dimensional optimization methods, resulting in significant technical shortcomings: First, surface coating modification alone can only alleviate surface wear in the short term; after long-term fluid scouring, the coating peels off entirely, failing to address the internal cracking and fragmentation of the activated carbon carrier, and the pulverization inhibition effect rapidly diminishes with operating time. Second, relying solely on a single inorganic binder to enhance particle strength results in an overly rigid binder layer with no buffering capacity; under the shear impact of oil, the binder interface is prone to cracking, still generating a large amount of powder. Third, simply expanding and reconstructing the pores of the activated carbon carrier without optimizing the particle interface bonding strength and outer protective structure means that powder generated by inter-particle friction cannot be effectively suppressed. These single modification methods can only partially alleviate powder generation and cannot form a complete protective system from the carrier interior, particle interface, and material surface. After long-term operation, the reduction in desulfurizer powder shedding rate is limited, failing to fundamentally solve the problems of downstream filter clogging and high maintenance costs.

[0005] Meanwhile, existing modification technologies do not have a self-healing protective structure designed for the liquid phase desulfurization of bio-jet fuel. After the surface of the desulfurizing agent is worn and damaged, there is no automatic repair mechanism, and tiny gaps will continue to expand, with submicron powder continuously escaping. Conventional modification processes are prone to causing blockage of activated carbon channels and a decrease in specific surface area, sacrificing the adsorption capacity of sulfides, and failing to meet the dual requirements of high strength, low pulverization and efficient desulfurization. Summary of the Invention

[0006] To address the technical problems mentioned in the background section, this invention provides a low-pulverization, high-strength bio-jet fuel desulfurization activated carbon, employing the following technical solution:

[0007] A low-pulverization, high-strength bio-jet fuel desulfurization activated carbon uses columnar activated carbon loaded with copper salt complexed desulfurization active components as the matrix, adapted to the liquid-phase adsorption desulfurization conditions of bio-jet fuel. The desulfurization activated carbon adopts a three-layer integrated synergistic modification structure, consisting of an internal pore reinforcement layer, a rigid-flexible composite bonding layer between particles, and a self-healing anti-pulverization surface layer on the outer surface of the particles. The internal pore reinforcement layer is a three-dimensional interlocking framework of rare earth aluminum silicate whiskers grown in situ in the micropores and mesopores of the activated carbon, used to fill and seal the original brittle microcracks of the activated carbon and maintain the adsorption specific surface area of ​​the carrier. The rigid-flexible composite bonding layer is an inorganic-organic interpenetrating network formed by cross-linking inorganic aluminum silicate sol and oil-resistant organic polymers, which has the dual functions of rigid support and fluid shear buffer. The self-healing anti-pulverization surface layer is a dense aluminum silicate protective film with embedded rare earth active sites. When the surface layer is locally damaged by oil erosion, the rare earth sites in the film can induce micro-crosslinking and self-healing of the surrounding aluminum silicate components. Hourly continuous liquid-phase scouring test of bio-jet fuel showed that the powder shedding rate of the desulfurized activated carbon was reduced by more than 50% compared with unmodified commercial desulfurized activated carbon, and the sulfur content of the desulfurized jet fuel was stable at ≤1ppm.

[0008] This three-layer synergistic modification structure differs from conventional modification methods in the industry that only involve single coating, single bonding reinforcement, or single pore reconstruction. It forms a complete anti-pulverization closed loop from three dimensions: the internal crack source of the carbon carrier, the inter-particle friction interface, and the erosion protection of the outer surface of the particles. It will not block the adsorption pores of activated carbon and ensure that the active components of copper salt can fully contact the oil to achieve deep desulfurization. It can also effectively inhibit the migration of submicron powder with liquid jet fuel to the downstream filter dehydrator, significantly extend the service life of the coalescence and separation filter element, reduce the frequency of unit shutdown and maintenance and the cost of operation and maintenance materials, and perfectly adapt to the harsh industrial conditions of long-term high-flow-rate oil erosion in the HEFA process sulfur absorption tank.

[0009] Furthermore, rare earth aluminosilicate whiskers are arranged in a staggered pattern along the axial direction of the activated carbon channels, and the whiskers overlap to form a three-dimensional support network. After channel strengthening modification, the specific surface area of ​​the activated carbon carrier is not less than 900 m². 2 / g, the pore structure was not blocked and the sulfide adsorption capacity did not decrease;

[0010] Rare earth aluminum silicate whiskers grow in situ within the micropores and mesopores of activated carbon, forming a continuous three-dimensional support network through interlocking. This network fills the inherent brittle microcracks in the activated carbon, enhancing the overall mechanical strength of the carbon carrier from within. The entire modification process generates whisker skeletons only on the inner walls of the pores, without blocking fluid mass transfer channels. After modification, the carrier retains ≥900 μm. 2 With a high specific surface area of ​​ / g, it can ensure uniform loading of copper salt desulfurization active components and full diffusion and adsorption of organic sulfides, completely solving the defects of conventional pore enhancement methods that easily cause pore blockage and desulfurization adsorption performance decline.

[0011] Furthermore, the inorganic silica-alumina sol is an acidic silica-alumina composite sol with a silica-alumina molar ratio of 1:1.5 to 1:3, and the oil-resistant organic polymer is a polyacrylol polymer that is resistant to the swelling of aromatics and alkanes. After the two are mixed and cross-linked, they fill the gaps between activated carbon particles to offset the shear stress generated by particle collision and friction, while resisting the continuous scouring of high-speed aviation kerosene fluid.

[0012] Inorganic silica-alumina sol provides rigid inorganic framework support, while oil-resistant polyacrylamide polymers have flexible buffering properties. After cross-linking, the two form an interpenetrating network that combines rigidity and flexibility, filling the gaps between carbon particles. The inorganic components enhance the overall compressive strength and wear resistance of the particles, while the organic polymers can absorb the impact and shear forces generated by oil scouring and particle collisions. This avoids the drawbacks of single inorganic bonding, which is hard, brittle, and prone to cracking, and single organic bonding, which has poor scouring resistance. In the long-term liquid phase environment of bio-jet fuel, the bonding structure will not be damaged by the swelling of hydrocarbon media, and the amount of powder generated by particle friction will be continuously reduced.

[0013] Furthermore, the thickness of the self-healing anti-powdering surface layer is controlled at 10~50μm, and rare earth active sites are uniformly dispersed inside the silicon-aluminum protective film. When the surface wears out and there are tiny gaps, the rare earth elements catalyze the silicon-aluminum hydroxyl groups to undergo condensation cross-linking, automatically repairing the surface damage and continuously inhibiting the shedding of submicron powder.

[0014] Within this thickness range, the silicon-aluminum protective membrane will not be too thick to block the pores on the surface of carbon particles and affect the contact between the oil and the internal desulfurization active components, nor will it fail due to rapid wear due to excessively thin membrane layers. The rare earth active sites evenly distributed within the membrane can serve as catalytic centers, continuously stimulating the silicon-aluminum hydroxyl condensation reaction in the liquid medium environment of jet fuel. Once erosion causes minor damage to the surface layer, cross-linking repair can be completed in real time, maintaining the integrity of the outer protective barrier of the particles for a long time, and preventing the stripping of submicron-sized carbon powder from the source and its entry into the downstream filtration system with the oil.

[0015] Furthermore, the columnar activated carbon is selected from industrial coal-based columnar activated carbon with a particle diameter of 3-6 mm. The copper salt complex desulfurization active components are uniformly loaded inside the activated carbon channels to adsorb and remove trace organic sulfur compounds in bio-jet fuel.

[0016] Coal-based columnar activated carbon has well-developed pores and superior mechanical strength compared to coconut shell and wood-based activated carbon. Its 3-6mm particle size is suitable for the fixed bed filling conditions of sulfur absorption tanks, ensuring oil flow and reducing bed pressure drop while minimizing particle tumbling and collision frequency. Copper salt complexed active components are deeply embedded in the carbon's internal pores and evenly dispersed. Relying on the high specific surface area of ​​activated carbon, sufficient adsorption sites are constructed, which can efficiently capture trace organic sulfur in bio-jet fuel and stably reduce the total sulfur in oil to below 1ppm, meeting the desulfurization requirements of jet fuel products.

[0017] Furthermore, the desulfurization activated carbon is specifically designed for the bio-jet fuel sulfur absorption tank in the HEFA oil hydrogenation process, which can significantly reduce the desulfurization powder carried by liquid oil to the downstream filter dehydrator, and extend the replacement cycle of the matching filter element by more than double.

[0018] The high oil flow rate inside the HEFA process bio-jet fuel sulfur absorption tank exposes the desulfurization activated carbon to a harsh environment of intense scouring and particle friction. This product, through three-layer synergistic modification, inhibits powder generation at the source, significantly reducing the total amount of submicron carbon powder carried with the oil. This reduces the probability of powder clogging and agglomeration, and hinders the separation of filter elements. It not only lowers the cost of filter element procurement and consumables but also reduces the frequency of unit shutdowns caused by excessive filter element pressure differentials. This effectively improves the continuous and stable operation time of the bio-jet fuel unit and has significant industrial economic value.

[0019] Furthermore, the three-layer integrated synergistic modification structure simultaneously achieves carrier skeleton reinforcement, particle interface buffering, and surface erosion resistance and self-healing, which is different from the existing desulfurization activated carbon modification schemes that only have a single coating, a single bonding reinforcement, and a single pore expansion.

[0020] Existing modification technologies can only optimize the pulverization problem from a single dimension, failing to address the three main causes of pulverization: internal cracks in the carbon carrier, inter-particle friction, and surface erosion. The modification effect is prone to short-term decay. This invention couples a three-layer structure—pore whisker reinforcement, rigid-flexible composite bonding, and a self-healing protective film—into a holistic synergistic system. It internally seals the original cracks in the carbon matrix, buffers particle impact and shearing in the middle, and autonomously repairs erosion damage externally, forming a multi-level inhibition barrier throughout the entire powder generation process. This creates a complete solution that is completely different from existing single modification technologies, effectively reducing the amount of desulfurization activated carbon powder shedding in the long term.

[0021] Furthermore, the preparation method includes four sequential steps: carrier pore strengthening, composite bonding molding, self-healing surface curing, and active component loading.

[0022] S1. Strengthening of carrier pores: columnar activated carbon is impregnated with a weakly acidic hydrothermal liquid containing rare earth nitrates and boehmite. After a closed low-temperature hydrothermal reaction, it is washed with water, dried and pre-calcined to generate a three-dimensional interlocking framework of rare earth aluminum silicate whiskers in situ within the activated carbon pores.

[0023] S2. Composite bonding molding: The activated carbon powder with reinforced pores is fully mixed with silica-alumina sol and oil-resistant polyacrylol polymer binder, extruded into strips and dried at low temperature to form an inorganic-organic interpenetrating rigid-flexible composite bonding structure.

[0024] S3. Self-healing surface curing: The shaped carbon particles are impregnated with a silica sol impregnation solution containing rare earth oxide precursors, drained, and then calcined at medium temperature to form a self-healing silicon-aluminum protective film with embedded rare earth active sites on the outer surface of the particles.

[0025] S4. Active component loading: The surface-modified carbon particles are immersed in a copper salt complex impregnation solution, cured at a constant temperature, and then dried to obtain the finished product of low-powdering, high-strength desulfurization activated carbon.

[0026] Furthermore, in step S1, the hydrothermal reaction temperature is controlled at 120~160℃, the hydrothermal holding time is 4~6h, the pre-calcination temperature is 330~370℃, and the calcination atmosphere is air, which fully stabilizes the whisker skeleton structure in the pores.

[0027] Using low-temperature hydrothermal conditions of 120~160℃ can avoid the collapse of activated carbon due to high-temperature carbonization. The holding time of 4~6 hours can ensure that rare earth and aluminum components react fully and whiskers are uniformly precipitated in the carbon channels. The subsequent pre-calcination in an air atmosphere at 330~370℃ can remove the residual hydrothermal solvent in the channels, promote the solidification of rare earth aluminum silicate whiskers, improve the bonding strength between whiskers and the inner wall of carbon, prevent whisker detachment and failure during subsequent kneading and molding and oil washing, and stabilize the strengthening effect of the three-dimensional support network inside the carrier.

[0028] Furthermore, after extrusion molding in step S2, the drying temperature is 80~120℃, and the drying is carried out in stages with a gradient temperature increase to avoid the rapid loss of water in the adhesive layer, which would cause cracks and holes.

[0029] If a single high-temperature direct drying method is used, the moisture inside the bonding system will vaporize rapidly, easily forming pores inside the newly formed carbon strip and causing surface cracks, which greatly weakens the overall strength of the particles. By using a segmented gradient heating process of 80~120℃, the free water and bound water in the bonding system can be removed gradually. The moisture evaporation rate is stable and controllable, which can completely preserve the dense structure of the inorganic-organic interpenetrating bonding network, prevent cracks from occurring during the drying stage, and ensure the basic strength of the desulfurized activated carbon in terms of friction resistance and erosion resistance.

[0030] This invention has the following advantages: It breaks through the existing one-sided modification approach of desulfurization activated carbon, which only involves single coating, single bonding, or single pore reinforcement. It pioneers a three-layer integrated synergistic modification system: carrier pore whisker reinforcement, rigid-flexible composite bonding of particles, and rare earth self-healing protection on the outer surface. This system fills and seals the carbon's original brittle microcracks by in-situ growth of rare earth aluminosilicate three-dimensional interlocking whiskers within the micropores and mesopores of the activated carbon. Combined with the cross-linking of silica-alumina sol and oil-resistant polyacrylamide polymers to form a rigid-flexible interpenetrating buffer bonding network, it counteracts the powdering caused by particle impact and fluid shear. Simultaneously, a dense silica-alumina protective film with embedded rare earth active sites is constructed on the outer layer of the particles. When the surface layer is locally damaged by high-speed jet fuel, the rare earth sites within the film can immediately induce condensation micro-crosslinking of surrounding silica-alumina hydroxyl groups, achieving self-healing. This provides long-term, full-chain inhibition of submicron carbon powder shedding from the internal matrix of the powder generation, the particle contact interface, and the outer protective surface. The modification process does not clog the carbon pores and can stably maintain a thickness of 900m. 2 With a high specific surface area of ​​over / g and the original sulfide adsorption capacity, the sulfur content of the finished desulfurized aviation kerosene is stable at ≤1ppm. After 1,000 hours of liquid phase scouring test, the powder shedding rate is reduced by more than 50%, and the replacement cycle of downstream supporting filter elements is extended by more than double. This multi-layered powder suppression modification structure, which combines internal skeleton reinforcement, interface stress buffering, and in-situ self-healing in liquid phase, has no relevant disclosure in existing public technologies. It completely solves the inherent defects of traditional single modification schemes such as easy pore clogging, brittle bonding layer, and rapid failure of surface protection. The process conditions are mild and controllable, and it is suitable for the long-term high flow rate and harsh working conditions of HEFA bio-aviation kerosene sulfur absorption tank. Attached Figure Description

[0031] Figure 1 This is a schematic diagram of the layered cross-sectional structure of the desulfurization activated carbon of the present invention;

[0032] Figure 2 This is a schematic diagram of the microscopic SEM of the whiskers inside the activated carbon channels of the present invention. Detailed Implementation

[0033] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0034] I. Description of Experimental Materials and Basic Testing Equipment

[0035] 1. All raw material specifications

[0036] The matrix is ​​made of industrial 4mm coal-based columnar activated carbon, with dense micron-level brittle cracks inside, and a specific surface area of ​​964m². 2 / g, the pore strengthening reagents were lanthanum nitrate hexahydrate (rare earth source) and pseudoboehmite, which were prepared into a weakly acidic mixed hydrothermal fluid with pH=4.2. The bonding system used acidic silica-alumina sol with a silica-alumina molar ratio of 1:2 and aromatic / alkane-resistant polyacrylamide polymer powder. The surface coating material was silica sol containing cerium dioxide rare earth precursor. The desulfurization active component was industrial copper ammonia complex impregnation solution, which can directionally adsorb trace organic sulfur compounds in oil. The test medium was crude bio-jet fuel produced by industrial HEFA process, with an initial total sulfur content of 8~12ppm.

[0037] 2. Performance testing equipment

[0038] The equipment included a specific surface area and pore size analyzer, a scanning electron microscope, a fixed-bed liquid phase erosion simulation test device, an oil sulfur content analyzer, an online differential pressure monitoring instrument, a particle wear resistance tester, and an optical microscope (for observing changes in surface self-healing gaps). All long-term erosion tests were conducted under the following conditions: liquid jet fuel flow rate of 1.8 m / h, constant temperature of 60℃, and continuous operation for 1000 hours, completely replicating the actual operating environment of the factory's sulfur absorption tank.

[0039] II. Standardized and Unified Preparation Process

[0040] S1, Pretreatment to strengthen carrier pores

[0041] A measured amount of coal-based columnar activated carbon was completely immersed in a rare earth-pseudo-boehmite weakly acidic hydrothermal solution. A low-temperature hydrothermal reaction was carried out in a sealed reactor. After the reaction, the carbon was repeatedly rinsed with deionized water to completely remove residual free salt ions from the pores and prevent impurities from clogging the pores during subsequent calcination. After rinsing, the carbon was thoroughly dried by hot air circulation at 110°C to remove free moisture from the pores. Subsequently, the carbon was placed in an air-atmosphere tube furnace for pre-calcination, which allowed the rare earth and aluminum components in the pores to fully crystallize and generate an in-situ interlocking three-dimensional framework of rare earth aluminum silicate whiskers. This framework filled the original brittle microcracks in the activated carbon and improved the overall mechanical strength from the inside of the carbon.

[0042] S2, Rigid-Flexible Composite Bonding Extrusion Molding

[0043] The activated carbon with reinforced pores is crushed to a uniform powder size. Acidic silica-alumina sol and polyacrylamide oil-resistant polymer are mixed in a fixed ratio and kneaded at high speed for 30 minutes until the material forms a uniform plastic paste. The paste is then fed into an extruder to prepare 4mm diameter columnar wet carbon strips. Instead of direct high-temperature drying, the wet carbon strips are dried using a three-stage gradient temperature increase: 80℃→100℃→120℃. Free water is slowly removed in the low-temperature range, while bound water is steadily removed at the medium and high temperatures. This avoids instantaneous vaporization of moisture, which could cause pores and cracks in the internal and surface layers of the bonding layer. The inorganic-organic interpenetrating bonding network is fully preserved, balancing rigid compressive strength and fluid impact buffering performance.

[0044] S3, Self-healing silicon-aluminum protective surface curing

[0045] The dried and shaped carbon particles are completely impregnated with a silica sol impregnation solution containing rare earth cerium precursors. After being fully impregnated at room temperature for 30 minutes, excess sol on the surface is drained, and the particles are transferred to a calcination furnace and calcined at a constant temperature of 220~260℃ for 2~4 hours. The silica sol undergoes cross-linking and solidification, forming a dense protective film with a thickness of 10~50μm on the outer surface of the carbon particles. Rare earth active sites are uniformly dispersed and embedded in the film layer, providing catalytic active centers for self-healing of damage under liquid phase conditions.

[0046] S4, copper salt desulfurization active component loading

[0047] After surface curing, the carbon particles are immersed in a copper-ammonia complex impregnation solution and fully impregnated at a constant temperature of 40-60℃, so that the copper salt active components can be evenly diffused into the micropores and mesopores of the activated carbon. After impregnation, the carbon is dried and cured at 100-130℃, and finally the finished product, low-pulverization high-strength bio-jet fuel desulfurization activated carbon, is obtained.

[0048] III. Complete Preparation Parameters for Multi-gradient Examples and Three Sets of Control Samples

[0049] This invention sets up 5 gradient examples, adjusting the hydrothermal temperature, heat preservation time, pre-calcination temperature, surface film thickness, and medium-temperature curing temperature respectively. At the same time, 3 comparative examples are set up, corresponding to the existing mainstream single modification schemes in the industry and unmodified blank activated carbon respectively, intuitively demonstrating the creative advantages of the three-layer integrated synergistic modification of this invention.

[0050] Table 1. Complete preparation process parameters for Examples 1-5 and Comparative Examples 1-3

[0051]

[0052] IV. Multi-dimensional performance testing and detailed data analysis

[0053] (I) Pore structure and desulfurization adsorption capacity test

[0054] The most critical challenge in pore enhancement modification is that traditional high-temperature crystallization processes easily clog the micropores of activated carbon, directly reducing the sulfide adsorption capacity. This invention employs low-temperature hydrothermal in-situ whisker growth, forming a supporting framework only on the inner wall of the pores, without blocking fluid mass transfer channels. The BET test data for each group of samples are as follows:

[0055] Table 2. Pore structure and static desulfurization capacity test data of modified activated carbon

[0056]

[0057] As can be clearly seen from the data in Table 2, the specific surface area of ​​all embodiments of the present invention remained stably at 900 m² after modification. 2With a pore size of / g or higher, the average pore size was very similar to that of the blank control example 3, and the sulfide adsorption capacity showed only a very slight decrease. In contrast, the control examples 1 and 2, which only had a single coating and a single bonding, showed obvious pore blockage and a significant decrease in adsorption capacity, failing to meet the requirements of deep desulfurization production. Among them, Example 3 had the optimal pore structure, balancing mechanical strength and adsorption performance, and was the optimal implementation process of this invention.

[0058] (II) 1000-hour continuous liquid phase scouring dust suppression performance test

[0059] Simulating the long-term high-flow-rate oil scouring conditions of a sulfur absorption tank, the tank was continuously operated for 1000 hours. Carbon powder entrained in the downstream fluid was collected and weighed. The powder shedding rate and the proportion of powder reduction after removal were calculated, directly reflecting the product's ability to suppress powder carrying.

[0060] Table 3 Results of 1000-hour continuous rinsing powder shedding test

[0061]

[0062] Data shows that the comparative method of simply applying a single coating and bonding has a negligible effect on inhibiting powder removal, and a large amount of submicron carbon powder is still generated during operation. However, the powder removal rate of the five-layer gradient embodiment of the present invention is reduced by more than 50%, and the optimal embodiment 3 has a reduction of 66.4%. The root cause lies in the synergistic effect of the three-layer structure: internal whisker reinforcement of cracks, intermediate rigid-flexible bonding to buffer impact, and outer self-healing film to block peeling. A single modification scheme cannot achieve a multi-level closed loop of powder suppression.

[0063] (III) Desulfurization finished product indicators and downstream filter element service life test

[0064] The core requirements for bio-jet kerosene production are twofold: firstly, to achieve the required sulfur content in the product; and secondly, to reduce filter cartridge consumables and minimize downtime losses. The experiment used the same filtration and dehydration equipment, filled with the corresponding desulfurization activated carbon, and recorded the continuous operating time during which the filter cartridge pressure differential rose to the replacement threshold.

[0065] Table 4 Comparison of Oil Desulfurization Indicators and Filter Element Service Life

[0066]

[0067] (iv) Comparative test on surface rare earth self-healing

[0068] The core inventive feature of this invention is the in-situ micro-crosslinking self-healing achieved by embedding rare earth catalytic sites within the surface layer. No existing publicly available modified coating technologies possess this function. A standard 20μm damage defect was artificially created on the surface of all samples, which were then immersed in a simulated biological jet fuel liquid phase for 24 hours. The defect repair was observed under a microscope.

[0069] Table 5. Test data on the self-healing performance of the protective membrane in the liquid phase.

[0070]

[0071] The data fully validates the inventive difference: Comparative Example 1, which has a single coating without rare earth catalytic sites, has almost no self-healing effect. The surface damage gaps cannot be automatically filled, and the entire membrane falls off after long-term scouring, with a large amount of powder precipitated. In the embodiments of the present invention, rare earth active sites are uniformly dispersed in the membrane layer, which can continuously catalyze the condensation and cross-linking of silicon-aluminum hydroxyl groups in a liquid-phase jet fuel environment, automatically fill the scouring damage gaps, and continuously maintain an intact external protective barrier. Among them, Example 3, with a membrane thickness of 30μm, has the best self-healing effect and its long-term scouring resistance performance far exceeds that of existing modified products.

[0072] V. Microstructure Mechanism Analysis

[0073] Figure 1 The overall structure consists of four layers arranged sequentially from the inside out: a coal-based columnar activated carbon matrix framework; a rare earth aluminum silicate whisker channel reinforcement layer, where whiskers interlock within the carbon's micropores and mesopores to form a three-dimensional support network, sealing off original microcracks; a rigid-flexible composite bonding layer between particles, where inorganic silicon-aluminum and oil-resistant polymers interpenetrate and crosslink to buffer particle collisions and fluid shear forces; and an embedded rare earth active site self-healing silicon-aluminum protective surface layer, with uniformly dispersed rare earth self-healing active sites within the membrane. This three-layer modified structure is integrated and composite-formed, simultaneously blocking the powder generation path from the inside, interface, and surface, representing a core structural innovation that distinguishes it from existing single-modification schemes.

[0074] Figure 2 In the middle: Under scanning electron microscopy, a large number of needle-like rare earth aluminosilicate whiskers can be observed growing on the inner wall of carbon pores. The whiskers interlock to form a three-dimensional network, which only adheres to the pore wall and does not block the main fluid flow channel. This not only strengthens the brittle skeleton inside the carbon, but also completely preserves the adsorption mass transfer space, solving the defects of traditional filling modification that block pores and reduce desulfurization capacity.

[0075] VI. Pilot-scale Industrial Application Implementation Instructions

[0076] The low-pulverization desulfurization activated carbon prepared by the optimal process (implementation 3) was loaded into the sulfur absorption tank of the domestic HEFA oil hydrogenation bio-jet fuel demonstration unit for 2000 hours of continuous pilot-scale operation. The pressure difference of the tank bed, the pressure difference of the downstream filter dehydrator, the sulfur content of the oil, and the frequency of filter element replacement were monitored online throughout the process. During the pilot-scale operation, the overall pulverization of the desulfurizing agent was extremely low, and the rate of increase in the pressure difference of the downstream filter was reduced by 72% compared with the original ordinary desulfurization activated carbon. No downtime was required to replace the filter element during the 2000-hour operation cycle. The total sulfur of the bio-jet fuel was stably maintained at 0.5~0.7ppm, which fully meets the export-grade SAF product standard. The raw materials for the entire preparation process are conventional and readily available, and the hydrothermal and roasting temperature ranges are mild. No special high-pressure or high-temperature equipment is required. Existing activated carbon modification production lines can be easily modified to achieve large-scale production. It can be widely promoted to various bio-jet fuel liquid phase desulfurization units at home and abroad, with outstanding market and economic benefits.

[0077] VII. Comprehensive Summary of Implementation Results

[0078] Based on comprehensive microscopic characterization, long-term laboratory erosion tests, and industrial pilot-scale data, this invention differs from the fragmented modification approach of single coating, single bonding, and single pore reinforcement commonly used in the industry. It uniquely employs a three-layer integrated synergistic modification system: pore whisker reinforcement, rigid-flexible composite bonding, and rare-earth self-healing surface layer. This system constructs a complete powder suppression closed loop from three dimensions: internal cracks in the carbon matrix, particle friction interfaces, and external erosion protection, ensuring a 900m... 2 With a high specific surface area of ​​over / g and without sacrificing desulfurization adsorption capacity, it achieves a powder shedding rate reduction of over 50% and a doubling of filter cartridge service life. At the same time, it pioneers a liquid-phase in-situ self-healing protective membrane structure, solving the long-standing industry pain point of protective failure and continuous powdering in traditional modified products during long-term operation. The process is stable and easy to scale up, combining material structure innovation, functional innovation, and industrialization value.

[0079] This invention is simple to operate, convenient to use, and suitable for widespread promotion and application. Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions, and variations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A low-pulverization, high-strength activated carbon for desulfurization of bio-jet fuel, comprising columnar activated carbon loaded with copper salt complexed desulfurization active components as a matrix, adapted to the liquid-phase adsorption desulfurization process of bio-jet fuel, characterized in that, The desulfurization activated carbon adopts a three-layer integrated synergistic modification structure, consisting of an internal pore reinforcement layer, a rigid-flexible composite bonding layer between particles, and a self-healing anti-pulverization surface layer on the outer surface of the particles. The internal pore reinforcement layer is a three-dimensional interlocking framework of rare earth aluminum silicate whiskers grown in situ in the micropores and mesopores of activated carbon. The rigid-flexible composite bonding layer is an inorganic-organic interpenetrating network formed by cross-linking inorganic aluminum silicate sol and oil-resistant organic polymers. The self-healing anti-pulverization surface layer is a dense protective film of aluminum silicate with embedded rare earth active sites.

2. The low-pulverization, high-strength bio-jet fuel desulfurization activated carbon according to claim 1, characterized in that, The rare earth aluminosilicate whiskers are arranged in an interlaced pattern along the axial direction of the activated carbon channels, and the whiskers overlap to form a three-dimensional support network. After channel strengthening modification, the specific surface area of ​​the activated carbon carrier is not less than 900 m². 2 / g, the pore structure was not blocked, and the sulfide adsorption capacity did not decrease.

3. The low-pulverization, high-strength bio-jet fuel desulfurization activated carbon according to claim 1, characterized in that, The inorganic silica-alumina sol is an acidic silica-alumina composite sol with a silicon to aluminum molar ratio of 1:1.5 to 1:

3. The oil-resistant organic polymer is a polyacrylol polymer that is resistant to the swelling of aromatics and alkanes. After the two are mixed and cross-linked, they fill the gaps between activated carbon particles to offset the shear stress generated by particle collision and friction, while resisting the continuous scouring of high-speed aviation kerosene fluid.

4. The low-pulverization, high-strength bio-jet fuel desulfurization activated carbon according to claim 1, characterized in that, The thickness of the self-healing anti-powdering surface layer is controlled at 10~50μm. Rare earth active sites are uniformly dispersed inside the silicon-aluminum protective film. When the surface layer is worn and small gaps appear, rare earth elements catalyze the silicon-aluminum hydroxyl groups to undergo condensation cross-linking, automatically repairing the surface layer damage and continuously inhibiting the shedding of submicron powder.

5. The low-pulverization, high-strength bio-jet fuel desulfurization activated carbon according to claim 1, characterized in that, The columnar activated carbon is selected from industrial coal-based columnar activated carbon with a particle diameter of 3-6 mm. Copper salt complex desulfurization active components are uniformly loaded inside the activated carbon channels to adsorb and remove trace organic sulfur compounds from bio-jet fuel.

6. The low-pulverization, high-strength bio-jet fuel desulfurization activated carbon according to claim 1, characterized in that, The desulfurization activated carbon is specifically designed for the bio-jet fuel sulfur absorption tank in the HEFA oil hydrogenation process. It can significantly reduce the amount of desulfurization powder carried by liquid oil to the downstream filter dehydrator, and extend the replacement cycle of the matching filter element by more than double.

7. The low-pulverization, high-strength bio-jet fuel desulfurization activated carbon according to claim 1, characterized in that, The three-layer integrated synergistic modification structure simultaneously achieves carrier skeleton reinforcement, particle interface buffering, and surface erosion resistance and self-healing.

8. A method for preparing low-pulverization, high-strength bio-jet fuel desulfurization activated carbon according to any one of claims 1 to 7, characterized in that, The process includes four steps performed sequentially: carrier pore strengthening, composite bonding molding, self-healing surface curing, and active component loading. S1. Strengthening of carrier pores: columnar activated carbon is impregnated with a weakly acidic hydrothermal liquid containing rare earth nitrates and boehmite. After a closed low-temperature hydrothermal reaction, it is washed with water, dried and pre-calcined to generate a three-dimensional interlocking framework of rare earth aluminum silicate whiskers in situ within the activated carbon pores. S2. Composite bonding molding: The activated carbon powder with reinforced pores is fully mixed with silica-alumina sol and oil-resistant polyacrylol polymer binder, extruded into strips and dried at low temperature to form an inorganic-organic interpenetrating rigid-flexible composite bonding structure. S3. Self-healing surface curing: The shaped carbon particles are impregnated with a silica sol impregnation solution containing rare earth oxide precursors, drained, and then calcined at medium temperature to form a self-healing silicon-aluminum protective film with embedded rare earth active sites on the outer surface of the particles. S4. Active component loading: The surface-modified carbon particles are immersed in a copper salt complex impregnation solution, cured at a constant temperature, and then dried to obtain the finished product of low-powdering, high-strength desulfurization activated carbon.

9. The preparation method according to claim 8, characterized in that, In step S1, the hydrothermal reaction temperature is controlled at 120~160℃, the hydrothermal holding time is 4~6h, the pre-calcination temperature is 330~370℃, and the calcination atmosphere is air, which fully stabilizes the whisker skeleton structure in the pores.

10. The preparation method according to claim 8, characterized in that, After extrusion molding in step S2, the drying temperature is 80~120℃, and the drying is carried out in stages with a gradient temperature increase to avoid rapid water loss of the adhesive layer and the formation of cracks and holes.